Widely targeted metabolomics analysis reveals the dynamically changes in volatile metabolites during xiaoqu baijiu fermentation - Zhenbing Ma; Haibo Lan; Dong Zhao; Jingren Wei; Jia Zheng; Jian Su; Shengyuan Xiang; Zhu Luo; Rui Li; Yi Ma; Lijuan Gong (Food Chemistry: X)
Baijiu is prepared via solid fermentation and distillation, and volatile metabolites influence its flavor considerably. However, the volatile metabolites' transformational relationship during the fermentation process remains unclear. In this study, ultra-performance liquid chromatography–tandem mass spectrometry and gas chromatography–tandem mass spectrometry were used to analyze a widely targeted metabolome during the xiaoqu baijiu fermentation process. In total, 668 volatile metabolites comprising 16 subclasses were identified. Significant variations in metabolites were observed during the fermentation process, especially in the distillation stage, and the conversion intensity of volatile metabolites was consistent with the following order of stages: distillation > soaking > saccharification > fermentation > stewing. A total of 570 differential volatile metabolites were identified in the distillation stage, especially esters, terpenoids, and hydrocarbons. These results provide a theoretical basis that could guide the xiaoqu baijiu fermentation process based on desired quality and components.